METHODOLOGY FOR USING DIGITAL TECHNOLOGIES AND INTERACTIVE PLATFORMS IN TEACHING CHEMISTRY - Ishmanova Zohida Ubaydullayevna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation: This article examines the methodological foundations for integrating digital technologies and interactive platforms into chemistry education. In the context of rapid digital transformation, modern chemistry teaching requires innovative approaches that enhance conceptual understanding, experimental skills, and learner engagement. The study analyzes theoretical perspectives on digital pedagogy, explores various interactive platforms used in chemistry instruction, and proposes a structured methodological model for effective implementation. The research employs qualitative analysis of existing literature and comparative evaluation of digital tools in educational practice. The results indicate that digital technologies significantly improve visualization of abstract chemical processes, promote collaborative learning, and support differentiated instruction.